Inference and probability in methodology of Hadith - Shaari, Jesni Shamsul; Hashi, Abdurezak Abdulahi; Othman, Nurul Nabihah; Mohd Sutarzi, Nur Izatul Firdaus; Rozlin, Nor Atiqah (Kulliyyah of Science, IIUM, 2011)
A central feature in the study of hadith methodology is in ensuring the authenticity of a narration attributed to the Prophet (s.a.w). While the details of criterion may differ somewhat between scholars, the common principles would see scrutiny of the content of a hadith as well as the chain of transmission. It is thus with these that scholars are able to determine the condition of the reports attributed to the Prophet (s.a.w). In this work, we propose to model the transmission of hadith in the context of binary channels and use the Bayes theorem from basic Probability Theory to discuss authenticity of a narration in a quantitative language. We present the model and further apply it to analyze certain types of hadith, including the muttawatir and ahad. Keywords: hadith transmission, chain, probability theory, analysis